Reportajes mediante el periodismo científico para divulgar las investigaciones académicas de la Universidad Nacional de Loja - Caraguay Díaz, Mayra Yessenia (2023)
The central object of this research sought to identify the necessary conditions to generate reports through investigative journalism. Consequently, this study focuses on the delineation, formulation, and execution of a guide aimed at the dissemination and visibility of research projects emanating from the Faculty of Education at the National University of Loja. The utilization of a mixed-methods approach facilitated a holistic understanding by systematically collecting, interpreting, and analyzing a variety of data. This encompassed everything from evaluating the web observation matrix to conducting interviews with experts and engaging in conversations with the project leaders. The obtained results highlight the existence of a robust scientific output throughout the National University of Loja. However, this output remains largely unknown to the students of the institution. The lack of scientific outreach by the majority of the researchers emerges as a determining factor in this knowledge disparity. Keywords: Journalism, scientific dissemination, academia, research, investigative journalism.